Heterogeneity of Graphite Lithiation in State‐of‐the‐Art Cylinder‐Type Li‐Ion Cells. Issue 2 (23rd November 2020) - Petz, Dominik; Mühlbauer, Martin J.; Schökel, Alexander; Achterhold, Klaus; Pfeiffer, Franz; Pirling, Thilo; Hofmann, Michael; Senyshyn, Anatoliy
Abstract: The two‐dimensional lithium distribution in the graphite anode was non‐destructively probed by spatially resolved neutron diffraction for a batch consisting of 34 different cylinder‐type (18650) Li‐ion batteries in fully charged state. The uniformity of the lithium distribution was quantified and correlated to the cell specifications/electrochemistry and to intrinsic cell parameters like electrode thickness, position of current collectors, etc. which were obtained by X‐ray micro‐computed tomography. Non‐uniformities in the lithiation state of the anode from a constant plateau have been observed for the majority of the studied cells. Their location corresponds to the positions of current tabs connecting the electrode stripes and areas of incomplete electrode coating at the beginning and the end of the electrode stripes. Four commonly used schemes of current lid connection were identified. Each of them displays its own effect on the uniformity of the lithiation at the anode and, therefore, variation of the intrinsic state‐of‐charge distribution and, most probably, the ageing behavior of the electrodes. Abstract : Non‐destructive look : Using spatially resolved neutron diffraction the 2D lithium distribution in the graphite anode was non‐destructively probed for a batch of cylinder‐type (18650) Li‐ion batteries in fully charged state. Peculiarities of lithium distribution were correlated to the cell specifications/electrochemistry and to intrinsic cell parameters like electrode thickness, position of current collectors, etc., which were obtained by X‐ray micro‐computed tomography. A method for quantification of non‐uniformities in the lithiation of the graphite anode from a constant plateau has been proposed.